COVID-19-Positive Report Posing a Delay in Treatment Course in a Middle-Aged Metastatic Neuroendocrine Tumor Patient - Krishnapriya, V (Indian J Palliat Care, 2020)
The COVID-19 outbreak is an unexpected challenge to all areas of health-care delivery, including cancer centers. The novel coronavirus is known to affect individuals in all age groups, especially patients with multiple comorbidities. A nationwide lockdown has restricted the routine patient care, with health-care services focusing mainly on emergency services and COVID patient management. These restrictions in health services may delay the treatments of non-COVID patients. This conundrum is especially true in cancer patients as they require frequent visits to the hospital, and there is a lack of understanding of the treatment prioritization in cancer patients. In this case, we discuss the concerns faced by a 37-year-old male with neuroendocrine tumor of the anal canal who was tested COVID positive. His surgery was canceled following the report and was shifted to the COVID care facility. Best supportive care was given till further management.